Feasibility Analysis Of Strawberry Granary Business In Pandanrejo Tourism Village - Rahadiantino, Lienggar; Prasetyo, Banu; Rahmawati, Deti; Windiani; Harmadi, Sonny Harry Budiutomo (Indonesian Journal of Development Studies, 2022)
Applying appropriate Strawberry Barn business development strategies can encourage the development of community economic activities to create economic independence. This study aims to: analyze the feasibility strategy for a strawberry agro-tourism business, analyze the factors that support the sustainability of agricultural businesses, and analyze the factors that hinder the development of strawberry farming in Pandanrejo Village, Bumiaji District, Batu City. The research location was agrotourism picking strawberries in Pandanrejo Village, Bumiaji District, Batu City, East Java. Data were obtained by the method of observation, interviews and documentation. Validity data was tested by triangulation technique—research using descriptive analysis. The results show that the strategies that can be used to analyze the feasibility of a strawberry agro-tourism business are supporting the adequacy of agricultural materials, maintaining price stability, breaking the supply chain, and optimizing financial management capabilities for strawberry farmers and business actors.